Fintech Peer-To-Peer (P2P) Lending: Explanation For The Issues In Indonesia - Permatasari, Sheila Silvia; Julito, Kiko Armenita; Santosa, Safira Zakkiyah Dwi (Universitas 17 Agustus 1945 Jakarta, 2025)
Financial technology (fintech) in Indonesia is developing rapidly. This is demonstrated by the acceleration of digital development and transformation in this country. The interaction between society and financial services has evolved very quickly over the last few years. On October 9, 2023, there were 101 companies as the total of Fintech peer-to-peer lending companies which listed at Otoritas Jasa Keuangan (OJK) or Financial Service Authority. However, from 2018 to 2023, OJK was recorded as having blocked 6,680 illegal fintech lending companies. The illegal Fintech lending companies have many risks. This research will observe several fintech lending problems in Indonesia along with the explanations of why these things occur. A qualitative approach will be used as a method in this research with NVIVO 14 software as a tool for analyzing data. The results of this study have provided an explanation of several problems that occur in Indonesia regarding FinTech P2P lending. Several of these problems are outlined into five points including: unclear admin fees; illegal access obtained from borrowers; threats, slander, fraud, sexual harassment; data misuse, high interest rates without limits.